PENGARUH KUALITAS PRODUK, KUALITAS LAYANAN DAN PERSEPSI HARGA TERHADAP KEPUASAN PELANGGAN (Studi Pada Gracia Skin Clinic Semarang) - Meilawati Nur Wulansari, 14.05.51.0190; Widyasari, suzy (Students' Journal of Economic and Management, 2019)
The purpose of this study is to analyze the effect of product quality, service quality, and price perception on customer satisfaction of Gracia Skin Clinic Semarang. Population in this research is consumers of Gracia Skin Clinic Semarang. The number of samples studied is as many as 100 respondents who use sampling technique by purposive sampling. Data testing techniques used include validity test with factor analysis, reliability test with alpha cronbach, and multiple regression analysis. The results in this study indicate that product quality, service quality, and price perception has positive and significant effect on customer satisfaction of Gracia Skin Clinic Semarang. Variable which has the greatest influence on customer satisfaction is the product quality.